Atypical acute disseminated encephalomyelitis with systemic inflammation after a first dose of AztraZaneca COVID-19 vaccine. A case report - Bastide, Laure; Perrotta, Gaetano; Lolli, Valentina; Mathey, Céline; Vierasu, Ortensa-Irina; Goldman, Serge; Vandergheynst, Frédéric (Frontiers in Neurology, 2022)
Background Only a few cases of acute disseminated encephalomyelitis (ADEM) following coronavirus disease 19 (COVID-19) vaccination have been described since the beginning of the vaccination campaign. Results Here we report the first case of central nervous system (CNS) demyelination with systemic inflammatory findings on whole body 19-fluorodeoxyglucose positron emission tomography with computed tomography (FDG-PET/CT) following the ChAdOx1 nCoV-19 vaccine. Conclusions Clinicians should stay aware of potential new adverse events after immunization.